(untitled) (International Seven Journal of Multidisciplinary, 2024)
It includes aspects of collegiate management in the financial decentralization of programs that transfer resources to public schools - especially the Direct Money at School Program - PDDE, correlating this management model to the process of strengthening democratic management. The research sought to understand the conditioning factors involved in the democratic management processes of public schools in the state of Maranhão in terms of community participation in the management of financial resources from the PDDE Program between 2018 and 2020. The methodological perspective is based on field research in schools that have a regulated school cashier in the state public education network in the state of Maranhão, Brazil. The questions that guided the research were aimed at answering how the manager deals with the power of decision over the school’s resources, how he manages community participation in the application of resources and how he conceives the dimension of autonomy in the management of resources.